2012
DOI: 10.1038/emboj.2012.96
|View full text |Cite
|
Sign up to set email alerts
|

CTC1 deletion results in defective telomere replication, leading to catastrophic telomere loss and stem cell exhaustion

Abstract: The proper maintenance of telomeres is essential for genome stability. Mammalian telomere maintenance is governed by a number of telomere binding proteins, including the newly identified CTC1-STN1-TEN1 (CST) complex. However, the in vivo functions of mammalian CST remain unclear. To address this question, we conditionally deleted CTC1 from mice. We report here that CTC1 null mice experience rapid onset of global cellular proliferative defects and die prematurely from complete bone marrow failure due to the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
209
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(220 citation statements)
references
References 59 publications
(97 reference statements)
11
209
0
Order By: Relevance
“…However, a reliable antibody against endogenous CTC1 is not commercially available, and we were unsuccessful in our multiple attempts to generate antibodies against both human and mouse CTC1 (data not shown). To circumvent this difficulty, we performed IF microscopy using an anti‐STN1 antibody to visualize endogenous STN1, which we have shown previously to be a reliable marker to detect the endogenous CST complex (Gu et al., 2012). We found that STN1 is present exclusively in the nuclei of WT HCT116 cells, but in HCT116 CTC1 L1142H mutants, nuclear levels of STN1 are reduced (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a reliable antibody against endogenous CTC1 is not commercially available, and we were unsuccessful in our multiple attempts to generate antibodies against both human and mouse CTC1 (data not shown). To circumvent this difficulty, we performed IF microscopy using an anti‐STN1 antibody to visualize endogenous STN1, which we have shown previously to be a reliable marker to detect the endogenous CST complex (Gu et al., 2012). We found that STN1 is present exclusively in the nuclei of WT HCT116 cells, but in HCT116 CTC1 L1142H mutants, nuclear levels of STN1 are reduced (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Telomere‐FISH revealed progressive increase in the percentage of sister chromatids with greatly reduced or missing telomere signals, a phenomenon termed sister telomere loss (STL), on metaphase spreads from late passage R‐46‐5 mutant cells, but not WT cells (Crabbe, Verdun, Haggblom & Karlseder, 2004) (Figure 3f, g). Fragile telomeres, prominent in CTC1 knockout mouse cells and suggestive of telomere replicative defects, were not significantly increased above background levels in CTC1 L1142H RPE mutants (data not shown) (Gu et al., 2012). While telomere length also shortened progressively in serially passaged WT RPE cells, sister telomere loss was infrequent and did not significantly increase with serial passages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations